2009
DOI: 10.1152/ajpregu.90396.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction due to uteroplacental insufficiency decreased white matter and altered NMDAR subunit composition in juvenile rat hippocampi

Abstract: Uteroplacental insufficiency (UPI), the major cause of intrauterine growth restriction (IUGR) in developed nations, predisposes to learning impairment. The underlying mechanism is unknown. Neuronal N-methyl-d-aspartate receptors (NMDARs) are critical for synaptogenesis and learning throughout life. We hypothesized that UPI-induced IUGR alters rat hippocampal NMDAR NR2A/NR2B subunit ratio and/or NR1 mRNA isoform expression and synaptic density at day 21 (P21). To test this hypothesis, IUGR was induced by bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 97 publications
2
32
0
1
Order By: Relevance
“…Given the extent that myelination and synaptogenesis impact one another, it is not surprising that related decreases in myelination were evident in dorsal FOR and FIM neurons leading from hippocampal subareas that have experienced blunted synaptogenesis. The reduced myelination observed in the present study corroborates results from a study by Schober et al [57] which found reduced myelination in hippocampal subareas in 21-day-old rats growth restricted by placental insufficiency. Myelination, as measured by MBP-IR and/or LFB staining, was also reduced in the parasagittal and PVW, as well as the CC in FGR animals (more so with sFGR than aFGR).…”
Section: Discussionsupporting
confidence: 93%
“…Given the extent that myelination and synaptogenesis impact one another, it is not surprising that related decreases in myelination were evident in dorsal FOR and FIM neurons leading from hippocampal subareas that have experienced blunted synaptogenesis. The reduced myelination observed in the present study corroborates results from a study by Schober et al [57] which found reduced myelination in hippocampal subareas in 21-day-old rats growth restricted by placental insufficiency. Myelination, as measured by MBP-IR and/or LFB staining, was also reduced in the parasagittal and PVW, as well as the CC in FGR animals (more so with sFGR than aFGR).…”
Section: Discussionsupporting
confidence: 93%
“…N-methyl-D-aspartate receptors are centrally involved in hippocampal synaptic plasticity (34) and seem to be selectively targeted in the IUGR situation. Altered composition of glutamate receptor subunits was recently observed in the hippocampus of IUGR rats born from an uteroplacental insufficiency model (35) and N-methyl-Daspartate receptor subtype 2B (Grin2b) was increased in the hippocampus of prenatally stressed rats (36). Microarrays allowed us to deeper characterize the hippocampal transcriptomic hallmark in DEX-IUGR pups as well as the impact of maternal bLf.…”
Section: Maternal Lactoferrin For Iugr Ratsmentioning
confidence: 99%
“…7), may have implications for other early nutrient deficiencies, including copper deficiency, iodine/thyroid hormone deficiency, and the proteinenergy malnutrition found in intrauterine growth restriction. All are characterized by hypomyelination and abnormal cognitive function and are interrelated; copper deficiency induces iron deficiency, whereas both induce a hypothyroid state in the brain (4,25,54,55). Although iron deficiency is common to these perinatal nutrient deficiencies (4,50), the similarity of brain developmental defects suggests that hippocampal IGF signaling is likely impaired in all of these preclinical rodent models.…”
Section: Perspectives and Significancementioning
confidence: 99%